4C Skills, Must Have untuk Generasi “Gen Z” di Kampar, Provinsi Riau - Alawiyah, Siti Tuti; Harared, Nico (Indonesian Journal of Society Engagement, 2023)
The phrase "Gen-z" refers to the generation born between 1997 and 2012. This generation has a global mindset and sees technology as their fundamental necessity. In other words, Gen-Z already outperforms the previous generation in terms of ICT/ICT skills. However, not all of the archipelago's Gen Z are yet proficient in navigating the digital age. Furthermore, the abilities required to become a competent individual include more than just being qualified to utilize ICT. As a result, today's youth must be capable of critical thinking and problem solving, as well as communication, teamwork, and creativity. According to the facts on the ground, many young people still do not comprehend the four soft skills and do not recognize the necessity of possessing the soft skills known as the 4C talents. This community service intends to introduce these 4C abilities and how crucial they are for the generation living in the twenty-first century, the digitalization century.The results of this Community Service are, (1) students of MAN 2 Kampar-Riau understand critical thinking and problem solving, communication, collaboration, and creativity skills, (2) students improve their 4C skills, (3) Students able to implement these 4 skills in their daily lives since they got enlightened about the knowledge from the given PkM, (4). Another goal of this PkM is to create the younger generation, especially Gen Z, who are aware of the massive changes in this digital era, are digitally savvy and encourage them to think critically and be able to solve problems, communicate well and effectively, collaborate with teams, be innovative and creative.